Investigation of the information sources for the characterization of users in Online Social Networks - Barbosa, Carlos M. G. (2024)
Individuals interact in a complex way for discussions in online social networks and the characterization of the way in which their are organized is essential for understanding the debate that take place around specific issues. This work presents a methodology for the characterization of discussions in online social networks and the groups of users that promove them based on the addressed topics and the external sources used by their users for the construction of the argumentation conducted on specific issues. An analysis of Twitter around discussions about the Federal Supreme Court (STF) and the COVID-19 vaccination in Brazil shows that the methodology is able to advance in the understanding of the way in which information is produced and propagated, and in the differences between the way various groups of individuals use external sources of information.